Amézola, Gonzalo A. de (coord.) (2020). Enseñar Historia. Temas y problemas. La Plata: Universidad Nacional de La Plata, 143 páginas. - González, Ana Ruth (2021)
Fil: González, Ana Ruth. Universidad Nacional de La Plata.